Drying Technique Providing Maximum Benefits on Hydrogelling Ability of Avocado Seed Protein: Spray Drying - Bakhtiyar Azad Abdullah; Bulent Basyigit; Mehmet Karaaslan (Foods, 2023)
The current study focused on creating natural hydrogels consisting of mixtures of avocado seed proteins dried with different techniques and locust bean gum. Proteins were extracted from avocado seed by alkali and isoelectric precipitation methods. Avocado seed proteins were dried by five different drying methods, namely ambient drying, oven drying, vacuum drying, freeze drying, and spray drying. FT-IR spectra were used to analyze the chemical structure of proteins dried using various techniques. Additionally, hydrogel models were constructed in the presence of avocado seed proteins and locust bean gum to clarify the effect of drying techniques on their hydrogelling ability. The impact of drying techniques on the functional behavior of hydrogels was notable. The maximum water holding capacity values were detected in the hydrogel system containing spray-dried proteins (93.79%), followed by freeze-dried (86.83%), vacuum-dried (76.17%), oven-dried (72.29%), and ambient-dried (64.8%) counterparts. The swelling ratio was 34.10, 33.51, 23.05, 18.93, and 14.39% for gels in the presence of freeze-dried, spray-dried, vacuum-dried, oven-dried, and ambient-dried proteins, respectively. Additionally, the desirable values for the amount of protein leaking from the systems prepared using spray-dried (7.99%) and freeze-dried (12.14%) proteins were obtained compared to others (ambient-dried: 24.03%; oven-dried: 17.69%; vacuum-dried: 19.10%). Superior results in terms of textural properties were achieved in hydrogel models containing spray-dried and freeze-dried proteins. In general, hydrogel models exhibited elastic behavior rather than viscous properties; however, the magnitudes of elasticity varied. Furthermore, the success of gels containing hydrogel models containing spray-dried protein and locust bean gum in the bioactive compound delivery system was obvious compared with protein ones alone.